Hermeneutics of Islamic Legal Education Verses: Integrating the Exegesis of Ayat al-Ahkam into the Reconstruction of the Fiqh Curriculum in the Digital Era - Irwandi M. Zen; Andri Gunawan; Amir Mahmud (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
This article aims to examine the relevance of the hermeneutics of Islamic legal education verses through the integration of tafsir ayat al-ahkam into the reconstruction of the fiqh curriculum in the digital era. This study is motivated by the need to develop Islamic legal education that is not merely oriented toward the transmission of normative knowledge, but also fosters legal awareness, critical thinking skills, and responsiveness to the complexities of contemporary digital realities. A hermeneutical approach is employed as an epistemological framework to understand the meanings of ayat al-ahkam contextually, thereby bridging the gap between the revealed text and the needs of modern society. This research adopts a qualitative library-based method, utilizing hermeneutical analysis and content analysis of literature on Qur’anic exegesis, fiqh, and Islamic educational curriculum theories. The findings indicate that the integration of tafsir ayat al-ahkam into the fiqh curriculum can produce a learning model that is more dialogical, contextual, and transformative. Curriculum reconstruction requires a shift in orientation from a rote-learning approach focused on legal rulings toward the development of interpretative competence, digital literacy, and legal consciousness grounded in maqāṣid al-syarī‘ah. Consequently, fiqh education in the digital era can function as an instrument for cultivating a society capable of understanding Islamic law dynamically and responding effectively to contemporary challenges.